Encyclopedia of Tourism - Saveriades, Alexis (My University, 2024)
This encyclopedia is the most comprehensive and updated source of reference in tourism research and practice. It covers both traditional and emerging concepts and terms and is fully international in its scope. Some 769 entries by 871 internationally renowned experts from 124 countries provide a definitive access to the knowledge of tourism and its related fields. Users will find reliable and up-to-date definitions and explanations of the key terms of tourism in this reference book. Tourism is the largest industry in the world and is the main source of income for many countries. With the practical impact of worldwide tourism and the growing number of academic programs and institutions devoted to its education and research, this encyclopedia is the epicenter of this emerging and developing discipline.
Cyprus
Keywords: Cyprus; Tourism